The Representation of Orientalism in The Hate U Give Movie - Pratama, Ridho Adam; Tawakkal, Alamsyah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research aims to explain how Orientalism is represented in The Hate U Give movie through the main character of Starr Carter using the Orientalism theory by Edward Said. In this research, the researcher uses qualitative research and descriptive method. Furthermore, the researcher elaborates on the Postcolonial issue in the literary work using the Postcolonial approach. The data of this research is taken from The Hate U Give (2018) movie directed by George Tillman Jr. and its English subtitle that is downloaded from the website subscene.com. The researcher finds there are seven data representing five representations of Orientalism in The Hate U Give movie through Starr Carter. The first representation is “black” portrayed Starr’s action rules and appearance. The second representation is “violent” described through Starr’s choice of words. The third representation is “inappropriate” depicted through Starr’s relationship with her white boyfriend. The fourth representation is “powerless” illustrated through the difference of power and authority between Starr and a white cop. The fifth representation is “poor” displayed through the sad moment of Starr. The conclusion of this research is the five representations of Orientalism represented by Starr Carter in The Hate U Give (2018) movie are black, violent, inappropriate, powerless, and poor portrayed by Starr Carter in the negative and bad images.